Smart HVAC: Monitoring dan Kontrol Berbasis IoT dengan Fuzzy Logic Mamdani - Esa Aprillah; Yasri; Subhanjaya Angga Atmaja (Universitas Kebangsaan Republik Indonesia, 2024)
The development of the Internet of Things (IoT) has driven the implementation of more efficient automation systems, including HVAC (Heating, Ventilation, and Air Conditioning) control. This study designs and implements an IoT-based HVAC monitoring and control system using a NodeMCU ESP8266, DHT11 sensors, relays, webcams, and the Mamdani Fuzzy Logic algorithm integrated with the Blynk application. The case study was conducted in the CV. Sukses Berkarya office, which requires stable temperature and humidity. The system is able to read temperature-humidity data, process it using fuzzy logic, and automatically control the air conditioning. Furthermore, YOLOv8 integration with the webcam is used to detect the number of people in the room as an additional parameter. Test results show that the system can maintain the room temperature within the ideal range of 18–30°C, reduce energy waste, and facilitate remote monitoring and control. This study demonstrates that the combination of IoT, fuzzy logic, and visual detection can produce an adaptive, efficient, and user-friendly HVAC system.